Fe3O4 Magnetic Nanoparticles as Peroxidase Mimetics and Their Applications in H2O2 and Glucose Detection - Wei, Hui; Wang, Erkang (Analytical chemistry (Washington), 2008)
Artificial enzyme mimetics are a current research interest because natural enzymes bear some serious disadvantages, such as their catalytic activity can be easily inhibited and they can be digested by proteases. A very recently study reported by Yan et al. has proven that Fe3O4 magnetic nanoparticles (MNPs) exhibit an intrinsic enzyme mimetic activity similar to that found in natural peroxidases, though MNPs are usually thought to be biological and chemical inert (Gao, L. Z.; Zhuang, J.; Nie, L.; Zhang, J. B.; Zhang, Y.; Gu, N.; Wang, T. H.; Feng, J.; Yang, D. L.; Perrett, S.; Yan, X. Y. Nat. Nanotechnol. 2007, 2, 577−583). In the present work, we just make use of the novel properties of Fe3O4 MNPs as peroxidase mimetics reported by Yan et al. to detect H2O2. The Fe3O4 MNPs were prepared via a coprecipitation method. The as-prepared Fe3O4 MNPs were then used to catalyze the oxidation of a peroxidase substrate 2,2‘-azino-bis(3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS) by H2O2 to the oxidized colored product (see eq 1) which provides a colorimetric detection of H2O2. As low as 3 × 10-6 mol/L H2O2 could be detected with a linear range from 5 × 10-6 to 1 × 10-4 mol/L via our method. More importantly, a sensitive and selective method for glucose detection was developed using glucose oxidase (GOx) and the as-prepared Fe3O4 MNPs. The detection platforms for H2O2 and glucose developed in the present work not only further confirmed that the Fe3O4 MNPs possess intrinsic peroxidase-like activity but also showed great potential applications in varieties of simple, robust, and easy-to-make analytical approaches in the future.